2016
DOI: 10.7554/elife.20958
|View full text |Cite
|
Sign up to set email alerts
|

The angiopoietin-like protein ANGPTL4 catalyzes unfolding of the hydrolase domain in lipoprotein lipase and the endothelial membrane protein GPIHBP1 counteracts this unfolding

Abstract: Lipoprotein lipase (LPL) undergoes spontaneous inactivation via global unfolding and this unfolding is prevented by GPIHBP1 (Mysling et al., 2016). We now show: (1) that ANGPTL4 inactivates LPL by catalyzing the unfolding of its hydrolase domain; (2) that binding to GPIHBP1 renders LPL largely refractory to this inhibition; and (3) that both the LU domain and the intrinsically disordered acidic domain of GPIHBP1 are required for this protective effect. Genetic studies have found that a common polymorphic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
161
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(174 citation statements)
references
References 56 publications
13
161
0
Order By: Relevance
“…Therefore, many in vitro LPL activity assays and purification protocols use a bile acid, deoxycholate, to stabilize LPL (40, 50, 54 -58). In the presence of deoxycholate, nANGPTL4 inhibits LPL by a reversible, noncompetitive mechanism (40,54). Because LPL is known to have enhanced thermal stability within the biological fluids that contain bile acids, like serum and milk, we used them to better mimic physiological conditions in our kinetic assays (58,59).…”
Section: Site-specific Interactions Between Lpl and Angptl4mentioning
confidence: 99%
“…Therefore, many in vitro LPL activity assays and purification protocols use a bile acid, deoxycholate, to stabilize LPL (40, 50, 54 -58). In the presence of deoxycholate, nANGPTL4 inhibits LPL by a reversible, noncompetitive mechanism (40,54). Because LPL is known to have enhanced thermal stability within the biological fluids that contain bile acids, like serum and milk, we used them to better mimic physiological conditions in our kinetic assays (58,59).…”
Section: Site-specific Interactions Between Lpl and Angptl4mentioning
confidence: 99%
“…Second, GPIHBP1 expression is crucial for the margination of triglyceride-rich lipoproteins (TRLs) along capillaries (4), allowing LPL-mediated triglyceride hydrolysis to proceed. Finally, in vitro biochemical studies have demonstrated that the binding of LPL to GPIHBP1 stabilizes LPL's hydrolase domain and preserves catalytic activity-even in the presence of ANGPTL4, an LPL inhibitor protein (5,6). …”
Section: Introductionmentioning
confidence: 99%
“…ANGPTL4 consists of an N-terminal coiled-coil domain (ccd) and a C-terminal, fibrinogen-like domain. The N-terminal ccd of ANGPTL4 inactivates LPL by promoting dissociation of the active LPL dimer into inactive monomers (9,10). In this way, ANGPTL4 acts as a potent energy homeostasis switch causing reduced uptake of FAs from TG-rich lipoproteins in WAT during fasting (11,12).…”
mentioning
confidence: 99%
“…It was previously demonstrated that the N-terminal ccd of ANGPTL3 reduces the activity of LPL in oxidative tissues in the fed state, thus directing the flow of lipoprotein-derived FAs to WAT for storage (14). In molar terms, ANGPTL3 is a relatively weak regulator of LPL in comparison to ANGPTL4 (10,15,16). Recent studies have shown, however, that the effect of ANGPTL3 on LPL is greatly enhanced by ANGPTL8 (15,17,18).…”
mentioning
confidence: 99%